Investigation of Dry Sliding Wear Behavior of Pack Boriding Fe-Based Powder Metallurgy. Issue 208 (12th June 2020) - Fang, Huimin; Xu, Feng; Zhang, Guangsheng
Abstract: The powder compact was directly sintered by a pack boriding process to prepare a Fe-based material having a boride layer. The boriding process was carried out at 850 °C, 950 °C and 1050 °C for 3, 5 and 10 h. The morphology of the boride layer was observed by a metallographic microscope, and the thickness of the boride layer was measured. The surface hardness of the boride layer was measured by a Rockwell hardness tester, the phase composition of the boride layer was analyzed by X-ray diffractometer and the friction and wear properties of the sample were tested on the HT-1000 friction and wear tester. The results show that the boride layer was mainly composed of Fe2 B single phase, and its thickness was uniform and firmly bonded to the substrate. The thickness and hardness of the layer gradually increased with time and temperature. The binding force between the layer and the substrate would be decreased while the thickness of the layer was too thin or too thick. Boriding at 850 °C and 950 °C resulted with formation of Fe2 B phases, while FeB and Fe2 B boride phases occurred at 1050 °C. The boride layer has good wear resistance in the friction and wear experiments, the wear mechanism of the boride specimen is mainly the fatigue spalling caused by plastic deformation of microcracks, while the un-bored samples show severe oxidation and plastic deformation.